Efficient purification and metabolite analysis of radiotracers using high-performance liquid chromatography and on-line solid-phase extraction - Chitneni, Satish K.; Serdons, Kim; Evens, Nele; Fonge, Humphrey; Celen, Sofie; Deroose, Christophe M.; Debyser, Zeger; Mortelmans, Luc; Verbruggen, Alfons M.; Bormans, Guy M. (Journal of Chromatography A, 2008)
This study describes an efficient method using on-line solid-phase extraction (SPE) (Oasis ® HLB) for preparative HPLC purification of short-lived radiotracers for positron emission tomography (PET) and for HPLC analysis of radiotracers and their metabolites in cell homogenates, plasma and urine samples. The radiochemical purity of tracers (fluorine-18 labeled) purified using this method (Oasis ® column) was >99% compared to 90% when no Oasis ® column was used. Radiometabolites of several fluorine-18 and carbon-11-labeled tracers and one technetium-99m tracer were quantified in cell homogenates, plasma and urine samples. Samples were analyzed using Oasis ® column and analytical HPLC system without prior precipitation of proteins or removal of other biological matrices. The metabolites observed for the evaluated tracers were all polar relative to the unchanged tracer. The extraction repeatability was found to be good (RSD 2.2%) and recoveries of Oasis ® column/HPLC-injected radioactivity (plasma) were found to be high (mean recovery >91%). The same Oasis ® column was used for several times without back pressure build-up or decrease of the HPLC separation characteristics.